All diseased things are critics. Issue 1 (March 2020) - Stormer, Nathan
This essay argues that pathology as an analytical form functions as the ethical critique of mutual vulnerability. In the broad sense of assessing what is life-giving and life-taking, a sustained critical engagement with pathological forms circulating through public life positions the study of rhetoric as a kind of immunotherapy for democracy. In that sense, embracing pathology as a critical analytic accepts biopower (expansively construed) as the operative framework for politics, which would seem like a kind of surrender to life-under-assault as the landscape of power. However, if wounds and their pathologies are understood as ethically ambiguous, it is possible to envision the critical potential of pathologia not only as immunotherapeutic but also as constitutive of new configurations of being together. Contrasted with a conception of pathology that presupposes a fixed difference between vital and morbid conditions, it is suggested that pathology be more precisely considered as the ethically ambiguous project of defining vitality and life that is "more than normal."